Inequalities and convergence of health outcomes in South Asian countries - Kumar, Sumit (South East Asia Journal of Public Health, 2016)
For human development of South Asian countries, which houses more than one-fifth of worlds population, it becomes crucial to study health inequalities between and within these countries. The aim of this paper is to explore the extent of health inequalities and convergence of health outcomes as represented by life expectancy and infant mortality rates among the South Asian countries. The statistical methods Gini coefficient, ?, and ?-convergence analysis are utilized to study inequalities and convergence-divergence, which are well established in macro-economic growth analyses. For the study longitudinal data over the period 1996-2012 for Infant Mortality rate (IMR) and Life expectancy (LE) is utilized. The results of the analysis indicate that there have been large inequalities in IMR and these are still increasing among the countries. However, in case of LE the inequalities are small and are on decline over the period of time. Further, the tests for convergence reveal that the IMR and LE have not been converged in the period 1996-2012 and no convergence clubs has been formed. The present analyses high-lights that the relative positions of countries among the South Asia have changed little and the trend of large inequalities among the countries continues. Further research to identify economic and social policy measures which decline the large inequalities among the countries can be rewarding exposition for all the stakeholders. South East Asia Journal of Public Health Vol.5(2) 2015: 71-76